EFFECT OF COVID-19 ON LOAN REPAYMENT OF SMALL BUSINESSES IN KENYA: A CASE STUDY OF EASTLEIGH BUSINESS COMMUNITY - Noor, Fidow Abdikadir (European Journal of Business and Strategic Management, 2020)
Purpose: The aim of this research is to investigate empirically the effect of pandemic outbreaks on loan repayment of small enterprises in Eastleigh business community, with particular focus for those who used borrowed fund in starting and operating their businesses. Design/methodology/approach: The target population of the study was the business community of Eastliegh, and samples of 50 businesses were randomly selected from the population. descriptive statistics were used to analyze the mean, mode, median, and the variance of the collected data. Regression and correlation were used to analyze the strength and the direction between the relationships of the different variable. Findings: The research results indicated statistically significant negative relationship between pandemic outbreak and loan repayment ability of small businesses in Easteigh, r(-.54), with p value of 0.008. Unique contribution to theory, practice, and policy: Pandemic outbreak affects business performance and survival in different ways. Small business owners, regulators, lenders, and the general public may benefit from this research by considering the impact of disruptions on small businesses. The study is one of the first to respond to the effect pandemic outbreak on small businesses after covid-19 pandemic eruption. Conducting this study was indispensable because of the importance of small businesses for the economy of any country and the current situation of covid-19 pandemic impact on them, specifically those who borrowed the fund they had invested.